If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 10 = 10 + -6x Reorder the terms: 10 + 4x = 10 + -6x Add '-10' to each side of the equation. 10 + -10 + 4x = 10 + -10 + -6x Combine like terms: 10 + -10 = 0 0 + 4x = 10 + -10 + -6x 4x = 10 + -10 + -6x Combine like terms: 10 + -10 = 0 4x = 0 + -6x 4x = -6x Solving 4x = -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 4x + 6x = -6x + 6x Combine like terms: 4x + 6x = 10x 10x = -6x + 6x Combine like terms: -6x + 6x = 0 10x = 0 Divide each side by '10'. x = 0.0 Simplifying x = 0.0
| 3x-10=5x-10 | | 5+11x=95 | | (5+2i)+(3+6i)= | | q-5-2=7-q | | 12+2.4c=22.5 | | 42=-3(1+5x)-3(3x+1) | | 22*16= | | 1.3=5980000000000000000000000000/x | | 5x+15(22+9x)=50 | | (x-2)*180=3240 | | 2sin^2x=-sinx | | 1-cos(t)=1.5 | | 1-cos(2t)=1.5 | | 3(4x+5)+2(x-7)+6x= | | 16x^5=81x | | x^6+8x^3+16=0 | | y-6=-3(x-4) | | f(t)=-5t+20t+60 | | 5(-7)-2(-3)= | | -30a-5a= | | -5=-11u | | 3x^2+5xy+y^2-4=0 | | x+9+x= | | Log(x)=3.4 | | 8-6(1-9f)=-30 | | ab=5-5c | | 4r^4-8r^2+16= | | 0.3(3x-12)+11=1+1.5x | | 7x-12=15+4x | | 4r^4-8r^2=16 | | 8x+5=13x-6 | | x(6+10)=58 |